Quaternary morpho-stratigraphic evolution of the eastern Campo Imperatore basin (Gran Sasso range, central Italian Apennines) and tectonic implication - Paolo Galli; Paolo Messina; Biagio Giaccio; Edoardo Peronace (Journal of Maps)
Geological survey and geochronological analyses were conducted in the Campo Imperatore plain to understand its Quaternary morpho-sedimentary and tectonic evolution. In the Late Pliocene-Early Pleistocene, low relief energy and steady and warm climatic conditions promoted a long phase of areal peneplanation, resulting in the formation of gently sloping landscape. With further regional uplift and changes in frequency/amplitude of the glacial-interglacial cycles (Early-Middle Pleistocene transition) and after establishment of the expansion-contraction cycles of the Apennine glaciers (Middle Pleistocene), the morpho-sedimentary processes become highly dynamic. In Middle Pleistocene, more than 100 meters of breccias deposited all along the slopes of the Gran Sasso range, followed by higher frequency processes of sedimentation, erosion and pedogenesis of Middle-Late Pleistocene to Holocene fluvio-glacial deposits. These have been progressively offset by synthetic and antithetic normal faults belonging to the Gran Sasso fault system, a 40-km-long seismogenic structure which released in the past earthquakes of Mw~7.